Students’ scientific attitude during the Implementation of innovative green garden-based education - Desy Fajar Priyayi; Gamaliel Septian Airlanda; Dina Rotua V. Banjarnahor (University of Muhammadiyah Malang, 2020)
Scientific attitudes are considereble aspect to observe in science learning. This study aimed to analyze students' scientific attitudes. In accordance with this aim, the students’ and teachers’ perceptions were recorded. This study was conducted in Junior High School 8 Salatiga. The sample of this research was 33 students and four science teachers. Furthermore, the quantitative data of scientific attitudes were collected using a questionnaire which than were analyzed using mean score. Meanwhile, the qualitative data of students' scientific attitudes and perceptions were collected by interviewing students and teachers. The results of the study showed that the scientific attitudes were catagorized in the range of mean score from 3.2 to 4.7. In addition, the students and teachers showed positive perceptions. To sum up, the green garden-based education could be an alternative model in science learning.